A founder MYBPC3 mutation results in HCM with a high risk of sudden death after the fourth decade of life. Issue 5 (4th March 2015) - Calore, Chiara; De Bortoli, Marzia; Romualdi, Chiara; Lorenzon, Alessandra; Angelini, Annalisa; Basso, Cristina; Thiene, Gaetano; Iliceto, Sabino; Rampazzo, Alessandra; Melacini, Paola
Abstract : Background: Mutations in the cardiac myosin binding protein C ( MYBPC3 ) gene account for a significant proportion of patients affected with hypertrophic cardiomyopathy (HCM). The aim of this study was to evaluate the penetrance and the impact of a frequent founder MYBPC3 mutation on HCM clinical expression and prognosis. Methods and results: Mutation screening of MYBPC3 gene was performed in 97 HCM probands. Nineteen (19.5%) resulted to be carriers of the founder p.F305Pfs*27 mutation and other 45 mutation carriers were identified during the evaluation of 14 families. Eleven (38%) mutation carriers were diagnosed between ages 30 years and 40 years. Disease penetrance was incomplete (64.4%), age-related and was greater in men than women (85% vs 48%, p=0.009). Probands carrying the founder mutation exhibited highest prevalence of non-sustained ventricular tachycardia (63% vs 22%, p=0.003; 63% vs 23%, p=0.01) and implantable cardioverter-defibrillator (58% vs 17%, p=0.001; 58% vs 18%, p=0.005) when compared with probands without MYBPC3 mutations or carrying other MYBPC3 mutations. Reduced survival due to sudden cardiac death (SCD) or aborted SCD occurred more frequently after the fourth decade of life in probands carrying p.F305Pfs*27 mutation than those without MYBPC3 mutations (32% vs 15%, p=0.01). Conclusions: p.F305Pfs*27 mutation carriers have a high probability to develop the disease between ages 30 years and 40 years with a significant major risk if they are men. This founder mutation is associated with an increase of SCD/aborted SCD events after the fourth decade of life.These findings are of relevant importance for management and clinical decision-making in patients with HCM.